AB0524 Design characteristics of the corrona certain study: A US comparative effectiveness and biomarker study of rheumatoid arthritis biologic agents. (23rd January 2014) - Pappas, D.A.; John, A.; Greenberg, J.D.; Devenport, J.; Kremer, J.M.; Ogale, S.; Reed, G.W.; Saunders, K.C.; Curtis, J.R.
Abstract : Background: Biologic agents have revolutionised the treatment of rheumatoid arthritis (RA). Few comparative, long-term data on treatment effectiveness and safety in the real world exist for patients typically seen in clinical practice. Objectives: To present the study design and baseline characteristics for 411 patients enrolled in the CORRONA CERTAIN study from 28 Oct 2010 to 30 Sept 2011. Methods: The CORRONA registry is a network of over 100 private and academic rheumatology practices across the US. The CORRONA CERTAIN is a comparative effectiveness prospective cohort study of adult patients with RA conducted across CORRONA participating sites. Patients with moderate disease activity (CDAI score >10) initiating a biologic agent (either for the first time or switching from a previous biologic) are eligible to enroll in CERTAIN. Physician and patient assessments, including lab values and biomarkers, are mandated at baseline, 3-, 6-, 9- and 12-month follow-up visits. A total of 2, 750 patients will be enrolled over 3 years. The primary endpoint of CERTAIN is CDAI <10, and comparative safety will also be evaluated. Results: Enrolled patients are 76.7% female, 84.3% Caucasian; median age is 56 (IQR: 47-64). Age, sex and race distributions are similar in TNF and nTNF cohorts. About 62% of the patients were initiated on a TNF and 38% on nTNF. Disease duration was 3 years (IQR: 1-8) for TNF cohort and 9 years (IQR: 3-16) for nTNF cohort. Biologic initiations included: etanercept (17.0%), adalimumab (16.5%), abatacept (16.3%), tocilizumab (15.8%), certolizumab (12.9%), infliximab (10.5%), rituximab (6.1%) and golimumab (4.9%). Monotherapy was used in 34.6% of TNF patients and 37.6% of nTNF patients. Fifty-four percent of TNF and 8.3% of the nTNF initiators were biologic naive. Among patients previously exposed to a different biologic, reasons for discontinuing the previous biologic were failure to maintain response (35%), minor side effect (12%), inadequate initial response (9%) and serious side effect (3%). For the TNF cohort, median baseline values were 25.0 (IQR: 17.0-34.0) for CDAI, 4.5 (IQR: 3.7-5.4) for DAS28 (CRP) and 5.0 (IQR: 1.7-10.8) for CRP. Corresponding values for the nTNF cohort were 29.0 (IQR: 23.0- 37.0), 5.0 (IQR: 4.3- 5.6) and 4.9 (IQR: 1.6-16.0). At baseline 14.9% of the TNF initiators and 9.7% of the nTNF initiators had total cholesterol >240 mg/dl. Among the patients enrolled, 30.4% had HTN, 8.5% had diabetes, 7.3% had a history of CVD and 5.4% reported a history of cancer. Conclusions: The CERTAIN study will generate comparative effectiveness and safety data to improve the quality of care and treatment outcomes for RA patients on biologics. Disclosure of Interest: D. Pappas: None Declared, A. John Employee of: Roche/Genentech, J. Greenberg Shareholder of: CORRONA, Consultant for: AstraZeneca, Novartis, Pfizer, CORRONA, J. Devenport Employee of: Roche/Genentech, J. Kremer Shareholder of: CORRONA, Grant/Research support from: Abbott, Amgen, AstraZeneca, BMS, Genentech, Lilly, Pfizer, Consultant for: Amgen, Genentech, Lilly, Pfizer, Employee of: CORRONA, Speakers Bureau: Abbott, Amgen, BMS, Pfizer, S. Ogale Employee of: Roche/Genentech, G. Reed Grant/Research support from: CORRONA, Consultant for: CORRONA, Employee of: University of Massachusetts Medical School, Paid Instructor for: Harvard Medical School, K. Saunders: None Declared, J. Curtis Grant/Research support from: Roche/Genentech, UCB, Centocor, BMS, Abbott, Amgen, CORRONA, Pfizer, Consultant for: Roche/Genentech, UCB, Centocor, BMS, Abbott, Amgen, CORRONA, Pfizer